Protoplanetary Disks as (Possibly) Viscous Disks - Rafikov, Roman R. (The Astrophysical journal, 2017)
Protoplanetary disks are believed to evolve on megayear timescales in a diffusive (viscous) manner as a result of angular momentum transport driven by internal stresses. Here we use a sample of 26 protoplanetary disks resolved by ALMA with measured (dust-based) masses and stellar accretion rates to derive the dimensionless -viscosity values for individual objects, with the goal of constraining the angular momentum transport mechanism. We find that the inferred values of do not cluster around a single value, but instead have a broad distribution extending from 10−4 to 0.04. Moreover, they correlate with neither the global disk parameters (mass, size, surface density) nor the stellar characteristics (mass, luminosity, radius). However, we do find a strong linear correlation between and the central mass accretion rate . This correlation is unlikely to result from the direct physical effect of on internal stress on global scales. Instead, we suggest that it is caused by the decoupling of stellar from the global disk characteristics in one of the following ways: (1) The behavior (and range) of is controlled by a yet-unidentified parameter (e.g., ionization fraction, magnetic field strength, or geometry), ultimately driving the variation of . (2) The central is decoupled from the global accretion rate as a result of an instability, or mass accumulation (or loss in a wind or planetary accretion) in the inner disk. (3) Perhaps the most intriguing possibility is that angular momentum in protoplanetary disks is transported nonviscously, e.g., via magnetohydrodynamic winds or spiral density waves.